UNVEILING THE DRIVERS OF SUSTAINABLE COMPETITIVE ADVANTAGE: A CUSTOMER RELATIONSHIP MANAGEMENT PERSPECTIVE - Amanda Amelinda; Hastin Umi Anisah (Adisam Publisher, 2026)
This study aims to examine the influence of Customer Relationship Management (CRM) components namely customer knowledge, customer orientation, and technology capability on sustainable competitive advantage from a customer perspective. The research addresses inconsistencies in prior findings regarding the effectiveness of CRM components in generating sustainable competitive advantage, particularly within the Islamic banking sector. A quantitative approach was employed using survey data collected from 110 customers of Bank Syariah Indonesia in Banjarmasin, focusing on Generation Z and millennial segments. The data were analyzed using SmartPLS 3.0 through structural equation modeling techniques. The results indicate that customer orientation and technology capability have a positive and significant effect on sustainable competitive advantage. In contrast, customer knowledge does not show a significant influence. These findings suggest that from the customer perspective the ability of firms to respond to customer needs and utilize technology plays a more critical role in creating unique and difficult to imitate value than merely possessing customer related knowledge. This study contributes to the CRM and Resource Based View literature by highlighting the contextual role of CRM components in shaping competitive advantage in Islamic banking.